Demographic and Psycho-Social Background as Correlates of Parents’ Perception of Causes of Mental Retardation among School Children in South-Western Nigeria (2011)
There are contradictory opinions surrounding the causes of mental retardation among parents of children with mental retardation. The causes on one hand may be genetic and on the other may be largely attributed to mystical forces. Previous studies have tried to ascertain the causes of mental retardation in families but they have not been able to establish the actual etiology. However, demographic and psychosocial factors are also important factors worthy of investigation in identifying the causes of mental retardation. This study, therefore, investigated the demographic and psycho-social background as correlates of parents‘ perception of the causes of mental retardation in 15 special education primary schools in South-Western, Nigeria. This study adopted a descriptive survey design of the ex-post facto type. Purposive sampling technique was used to select 606 respondents, 338 women and 268 men who were parents of children with mental retardation. These parents were met during Parent Teacher Association meeting at different occasions in all the schools. Data were collected using Parents‘ Perception of Mental Retardation Scale (r=0.68) and Mental Retardation Determinant Scale (r=0.77). Six research questions were answered and three hypotheses tested at the 0.05 level of significance. Data collected were analysed using multiple regression and analysis of variance. The psycho-social variables have a multiple correlation with the dependent variable (chances of giving birth to a child with mental retardation) (R=0.86). This joint correlation is shown to be significant (F(7,598)=247.48; p<0.05). The psycho-social variables accounted for 74.3% of the total variances in the chances of giving birth to a child with mental retardation. Three of the psycho-social variables have significant (p<0.05) relative contribution to the chances of giving birth to a child with mental retardation. These are cultural practices (β=0.36; t=15.92; p<0.05); birth order (β=0.09; t=3.65; p<0.05) and birth trauma (β=0.07; t=2.921; p<0.05). Socio-economic status and disease during the child‘s development have no significant relative contribution. It was also discovered that one in every three women that have children with mental retardation is between age 35 and 40. Large proportion of women (77.7%) that have children with mental retardation had no complication during pregnancy and (72.3%) had no difficulties during labour. Demographic and psycho-social variables were perceived to have jointly contributed to predicting mental retardation in children. Therefore, there is need for public enlightenment on the causes of mental retardation. Efforts should be made to educate and counsel parents of children with mental retardation on the causes and proper management of the condition.